2007
DOI: 10.1029/2005jb004161
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional velocity structures of Mount Fuji and the South Fossa Magna, central Japan

Abstract: [1] We present the three-dimensional structures of the P wave velocity (V P ), S wave velocity (V S ) as well as the P wave to S wave velocity ratio (V P /V S ) beneath Mount Fuji and the South Fossa Magna, Japan, using arrival time data collected from 2002 to 2005 by a dense seismograph array. The high-resolution data set and improved methodology reveal not only several velocity features that are consistent with previous studies but also important new details that clarify the velocity structures associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
57
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 41 publications
4
57
0
1
Order By: Relevance
“…We propose that fluid with high aspect ratio pores exists there, as proposed by Matsubara et al (2004Matsubara et al ( , 2009) based on the result of Takei (2002). Nakamichi et al (2007) and Kato et al (2010) also considered the high aspect ratio crack with low-V p /V s zone. If a large seamount has already subducted beneath the plate, a low-V zone would be imaged (Cummins et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…We propose that fluid with high aspect ratio pores exists there, as proposed by Matsubara et al (2004Matsubara et al ( , 2009) based on the result of Takei (2002). Nakamichi et al (2007) and Kato et al (2010) also considered the high aspect ratio crack with low-V p /V s zone. If a large seamount has already subducted beneath the plate, a low-V zone would be imaged (Cummins et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The seismic velocity tomography revealed that a lowvelocity wedge exists between the Tanzawa Mountains and Mount Hakone (Nakamichi et al, 2007;Nagai and Tanada, 2010). These studies interpreted the low-velocity wedge as trough-filled deposits, which accreted between the Tanzawa and Izu block.…”
Section: Discussionmentioning
confidence: 99%
“…According to our numerical modeling, the dilatation induced by the Hokodu-oki earthquake around Mount Fuji is about 220 nano-strains. Because of the existence of basaltic magma at depths of 15-25 km beneath Mount Fuji [3], exsolution of water is less likely. Therefore, volumetric expansion may lead to magma ascension and increase the risk of volcanic eruption.…”
mentioning
confidence: 99%
“…Mount Fuji is located southwest of Tokyo, on the border between Shizuoka and Yamanashi prefectures in central Honshu. The 3-D P-and S-wave velocity structures suggest existence of supercritical volatile fluid, such as H 2 O and CO 2 , at depths of 7-17 km beneath Mount Fuji, and there might be partial melting of basaltic rocks at depths of 15-25 km [3]. Changbaishan volcano is located at the border between NE China and North Korea and has been active in the past.…”
mentioning
confidence: 99%